Constructional materials experimental researches on the helium ions linear accelerator - Butenko, V.I.; Dubniuk, S.N.; Dyachenko, A.F.; Коbets, А.P.; Manuilenko, O.V.; Pavlii, K.V.; Soshenkо, V.A.; Tishkin, S.S.; Zajtsev, B.V. (Вопросы атомной науки и техники, 2021)
The basic parameters of an irradiation and their registration system for constructional materials irradiated on the helium ions linear accelerator are resulted. Experimental techniques and some researches results of the microscopic, electrophysical, frictional and ultrasonic characteristics of atomic power stations (APS) and fusion reactors (FR) constructional materials irradiated on a linear accelerator of the helium ions with energies 0.12 and 4 MeV are presented.